The Acute Phase Response Is a Prominent Renal Proteome Change in Sepsis in Mice - Róka, Beáta (Int J Mol Sci, 2019)
(1) Background: Sepsis-induced acute kidney injury (AKI) is the most common form of acute kidney injury (AKI). We studied the temporal profile of the sepsis-induced renal proteome changes. (2) Methods: Male mice were injected intraperitoneally with bacterial lipopolysaccharide (LPS) or saline (control). Renal proteome was studied by LC-MS/MS (ProteomeXchange: PXD014664) at the early phase (EP, 1.5 and 6 h after 40 mg/kg LPS) and the late phase (LP, 24 and 48 h after 10 mg/kg LPS) of LPS-induced AKI. Renal mRNA expression of acute phase proteins (APP) was assessed by qPCR. (3) Results: Renal proteome change was milder in EP vs. LP. APPs dominated the proteome in LP (proteins upregulated at least 4-fold (APPs/all): EP, 1.5 h: 0/10, 6 h: 1/10; LP, 24 h: 22/47, 48 h: 17/44). Lipocalin-2, complement C3, fibrinogen, haptoglobin and hemopexin were the most upregulated APPs. Renal mRNA expression preceded the APP changes with peak effects at 24 h, and indicated renal production of the majority of APPs. (4) Conclusions: Gene expression analysis revealed local production of APPs that commenced a few hours post injection and peaked at 24 h. This is the first demonstration of a massive, complex and coordinated acute phase response of the kidney involving several proteins not identified previously.